Safety and efficacy of R21/Matrix-M vaccine against and eradicate malaria infection - Rahaded, Patricia Valery; Herawati, Fauna (Institute of Computer Science (IOCS), 2024)
Malaria continues to be a substantial health concern, characterised by elevated rates of illness and death. The development of resistance to existing treatments poses unique obstacles to infection control initiatives. To combat the increasing incidence of malaria, it is imperative to create malaria vaccines such as RTS,S/AS01 and R21/Matrix-M. This study conducted a systematic literature revieew to evaluate the safety and efficacy of malaria vaccines that are currently being developed, with a specific focus on the R21/Matrix-M vaccine. Applying the PRISMA criteria, we identified five studies that specifically examined the efficacy and safety of the R21/Matrix-M vaccination. The findings indicated that the R21/Matrix-M vaccine exhibits favourable tolerability and demonstrates substantial efficacy in clinical studies. Nevertheless, the scarcity of research on the R21/Matrix-M vaccine thus far emphasises the necessity for additional investigation to substantiate its efficacy in malaria treatment.